Power system resilience to floods: Modeling, impact assessment, and mid-term mitigation strategies. (February 2022) - Souto, Laiz; Yip, Joshua; Wu, Wen-Ying; Austgen, Brent; Kutanoglu, Erhan; Hasenbein, John; Yang, Zong-Liang; King, Carey W.; Santoso, Surya
Abstract: This article presents a methodology aimed at improving mid-term power system resilience at transmission substations in areas potentially affected by floods, combining hardening strategies and quantitative metrics. It takes into account flood forecasts from a hydrological model and the location of electrical equipment to perform impact assessment "as is" and with resilience planning strategies. Thus, the impact of floods on the grid is evaluated over a range of realistic flood scenarios, based on the accumulated cost and load energy unserved as metrics together with future transmission system expansion capacity projections. The mixed-integer linear programming formulation is aimed at minimizing accumulated cost and load energy unserved with optimal hardening of substations, assuming that any non-hardened substation disabled by flooding must be repaired. Furthermore, the methodology is demonstrated in the coastal area of Texas with simulations of floods based on the rainfall of Hurricane Harvey in 2017. Ultimately, the choice of the most appropriate mitigation strategies shall optimize resilience metrics and/or cost indicators with robustness over a range of scenarios. Highlights: Mid-term power system resilience improvements to floods at transmission substations. Impact assessment considering hydrological model and location of electrical equipment. Accumulated cost and load energy unserved used as metrics separately. Mixed-integer linear programming formulation for optimal hardening of substations. Case study: floods based on Hurricane Harvey's rainfall in the coastal area of Texas.